A Systematic Review of the Use of Intraoral Scanning for Human Identification Based on Palatal Morphology - Sanjana Santhosh Kumar; Rachel Chacko; Amritpreet Kaur; Gasser Ibrahim; Dongxia Ye (Diagnostics, 2024)
A common application for intraoral scanners is the digitization of the morphology of teeth and palatal rugae. Palatal scans are most commonly required to fabricate complete dentures and immediate transitional dentures and serve as a reference point for assessing orthodontic results. However, they are also frequently included by accident, even though the main purpose of intraoral scanning is to reconstruct dentition using computer-aided manufacturing (CAM). The literature shows that the identification of disaster victims has frequently involved palatal rugae impressions. As the skull provides sound insulation, the rugae are resistant to heat, chemicals, and stress. Antemortem data might be difficult to find during a forensic inquiry, particularly in disaster victim identification cases. In contrast with DNA and fingerprints, there is a greater likelihood of having a dental record that contains palatal scans. With specialized software, the scans can be exported as open stereolithography (STL) files. Considering that a full case consumes up to about 100 MB of hard drive space, long-term storage should not be an issue compared to a plaster model. Additionally, dentists widely use online databases to exchange data for smile design, implant registration, and orthodontic purposes. This will produce a digital database that grows quickly and is readily usable for forensic investigations. The uniqueness of forensic features is frequently challenged; however, palatal morphology’s unique trait could make it possible as it is characteristic of individuals as well as the most distinguishing factor. This review will highlight how rugae, palatal morphology, mirroring, superimposition, and geometrics can serve in forensic identification.